تاریخ و سیرت کی روشنی میں حضرت مغیرہ بن شعبہ رضی اللہ عنہ کے احوال و آثار: A Historical and Biographical Study of the Life of Al-Mughirah ibn Shu’bah (RA) - Din, Sahib; Adil, Hafiz Muhammad (Al-Irfan, 2025)
The document serves as a comprehensive historical account of Hazrat Mughira bin Shu’bah (RA), a prominent companion of the Prophet Muhammad (PBUH), detailing his pivotal role in the expansion and consolidation of Islamic governance and society. It traces his lineage, early life, and conversion to Islam, highlighting his dedication and strategic brilliance in various capacities, including as a diplomat, military leader, and governor of key regions like Basra and Kufa. Notable accomplishments include his significant contributions to the Islamic conquests of Persia and his leadership in battles such as Qadisiyyah and Nahawand, where his tactical expertise was instrumental in defeating formidable adversaries. The narrative also explores his ethical conduct, exceptional oratory skills, political sagacity, and adherence to Islamic values, presenting a nuanced portrait of a leader who exemplified resilience, wisdom, and faith. Additionally, the text provides insights into the socio-political challenges of the time and their resolution through the principles of justice and accountability, offering enduring lessons for governance and leadership in Islamic history.